The role of common bile duct exploration with biliary drainage in choledocholithiasis during pregnancy - Gadang Ryan Dewantoro; Putra Gelar Parlindungan (Universitas Muhammadiyah Surabaya, 2023)
Pregnancy is a risk factor for gallstone disease and may evolve into symptomatic choledocholithiasis/ common bile duct (CBD) stone; however, the treatment of choice is controversial and may not apply to all gestational ages. Standard therapy with endoscopic retrograde cholangiopancreatography (ERCP) exposes the patient and fetus to ionizing radiation; hence other strategies are needed to address this problem. We report a case of 29 years old female presented with biliary pain and jaundice. The patient was pregnant at 14 weeks gestation age. Laboratory data showed biliary obstruction, and abdominal ultrasound showed multiple bile duct stones with significant dilatation in the CBD. CBD exploration with external biliary drainage was performed to treat obstructive jaundice while avoiding ionizing radiation exposure to the fetus and patient. After the procedure, the patient showed clinical improvement. CBD exploration with external biliary drainage avoids ionizing radiation in choledocholithiasis management. This method may be applied as a temporary emergent treatment of obstructive jaundice in pregnant patients with gestational age sensitive to ionizing radiation.